Reconciling economic concepts and person-centred care of the older person with cognitive impairment in the acute care setting - Rushton, Carole (Nursing philosophy, 2020)
Person-centred care is a relatively new orthodoxy being implemented by modern hospitals across developed nations. Research demonstrating the merits of this style of care for improving patient outcomes, staff morale and organizational efficiency is only just beginning to emerge. In contrast, a significant body of literature exists showing that attainment of person-centred care in the acute care sector particularly, remains largely aspirational, especially for older people with cognitive impairment. In previous articles, we argued that nurses work constantly to reconcile prevailing constructions of time, space, relationships, the body and ethics, to meet expectations that the care they provide is person-centred. In this article, we explore key concepts of neo-liberal thought which forms an important back-story to the articles. Economic concepts, "efficiency" and "freedom" are examined to illustrate how nurses work to reconcile both the repressive and productive effects of economic power. We conclude the article by proposing a new research agenda aimed at building a more nuanced understanding of the messy actualities of nursing practice under the influences of neo-liberalism, that illuminates the compromises and adaptations nurses have had to make in response to economic power.